The Solow-Pasinetti debate on the measurement of productivity in the light of modern growth theory - Florencia R. Sember (PSL Quarterly Review, 2024)
This article aims to study the Solow-Pasinetti debate on the aggregate production function and technical progress as an event that anticipated a divide in the subsequent theories of economic growth and technical change. Ultimately, the debate manifests two completely different approaches, not only to the particular question of technical change but also to political economy tout court. Pasinetti gave paramount importance to the fact that the factors of production could not be treated as symmetrical, as the neoclassical theory treated them. Related to this is Pasinetti's dismissal of the distinction neoclassical economics made between shifts in the production function to evaluate technical change and movements along it. In fact, he dismissed the neoclassical production function altogether.
Keywords: B22; B41; O40; 330; Pasinetti; production function; productivity measurement; Solow